Isolation and study of protein compounds from the fruits of beans, Phaseolus Vulgaris and cowpea Vigna Sinensis in normal and alloxan induced diabetic mice. - Nahida Chalabi; Shehab Al - Bajari (College of Education for Pure Sciences, 2012)
Abstract: This study is concerned with the preparation of cold and boiled aqueous extracts from the fruits of both Phaseolus Vulgaris and Vigna Sinensis plants. Then isolating and studying the active proteinous compounds from these extracts using different biochemical techniques. Precipitation of the proteinous part from each extract was was a ccomplished by cold acetone precipitation method. Two compounds (A) and (B) had been isolated from gel filtration chromatography of cold and boiled acetone precipitate of these fruits of both plants. The comparative molecular weights of the isolated compounds were estimated using gel filtration and found to be ranged from 1887 to 33884 daltons for all the Phaseolus Vulgaris and Vigna Sinensis. The work also included studyingf the effect of intraperitoneal administration of these compounds (A) and (B) on certain blood biochemical parameters (glucose, cholesterol and total lipids) using a dose of 77 mg/Kg of body weight in normal and alloxan. induced diabetic mice. The results had been compared with those injected with insulin. The proteinous compounds (A) which had been separated from (cold and boiled) of each Phaseolus Vulgaris and Vigna Sinensis led to a decrease in the level of glucose diabetic mice and also all compounds (B) for both plants. Compound (A) from cold extract of Vigna Sinensis fruit is more reduced for the glucose level (67.1%) from the other compounds and it reached to a normal level in the alloxan -induced diabetic mice when compared with normal control group. However, proteinous compounds (A) (cold and boiled) which have been separated from each Phaseolus Vulgaris and Vigna Sinensis fruits and also the compound B (cold and boiled of Vigna Sinensis fruit) have been showed a significant decrease in the biochemical parameter (cholesterol and total lipids in the blood serum of diabetic mice). These compounds have revealed an effect similar to that of insulin, but the compound A (which was separated from cold aqueous extract of Vigna Sinensis fruit) gave a reduction effect for the total lipids level (46.83%) more than of that for insulin and the other proteinous compounds mentioned. In conclusion, the high molecular weight compounds might be used for the treatment of diabetes mellitus instead of insulin, furthermore it could be used it in the treatment of atherosclerosis after make sure there is no side effects.